Impacto do uso droga imunomoduladora no tratamento da artrite séptica por Staphylococcus aureus - Machado, Priscila Maria Colavite [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Staphylococcus aureus is considered the more important etiological agent of septic arthritis. In this context, the main objective of this work was to investigate the arthritogenic capacity of standard S. aureus strains, producer of superantigens (SAgs). We also tested the therapeutic effectiveness of an association antibiotic and an immunomodulatory drug in this model. C57BL/6 male mice were initially infected by retro-orbital plexus with different strains. Development and severity of arthritis were followed during 14 days, through determination of body weight, clinical score and incidence of arthritis, histopathological changes, determination of colony forming units, evaluation of local infiltration of Th subsets by real time PCR and cytokine production by spleen cells. The results were organized in three manuscripts. In the first one we compared the arthritogenic ability of 5 S. aureus strains. We found that the strains ATCC 19095 SEC+, N315 ST5 TSST-1+ and S-70 TSST-1+ determined severe, intermediate and discrete arthritis, respectively. In the second study we characterized the arthritis caused by the ATCC 19095 SEC+ strain. This type of arthritis was characterized by high clinical scores associated with synovial proliferation, intense inflammation, pannus formation, cartilage destruction and bone erosion. In the final manuscript we evaluated the therapeutic potential of the combination bewteen cloxacilin (bactericidal antibiotic) with tacrolimus (immunomodulator). The administration of these two drugs was less effective in controlling the disease than the antibiotic alone

Staphylococcus aureus é considerado o agente etiológico mais importante da artrite séptica. Neste contexto, o objetivo geral deste trabalho foi investigar o potencial artritogênico de cepas padrão de S. aureus produtoras de superantígenos (SAgs) e testar a eficácia terapêutica da associação entre antibiótico e imunomodulador neste modelo. Camundongos C57BL/6 machos foram inicialmente infectados pelo plexo retro-orbital com as diferentes cepas. O desenvolvimento de artrite e sua gravidade foram acompanhados por 14 dias, através das seguintes determinações: peso corporal, escore clínico e incidência de artrite, alterações histopatológicas, número de unidades formadoras de colônias, expressão local de citocinas e subpopulação células por PCR em tempo real e produção de citocinas por células esplênicas. Os resultados foram organizados em 3 manuscritos. No primeiro, comparamos a capacidade artritogênica de 5 cepas produtoras de SAgs. Constatamos que as cepas ATCC 19095 SEC+, N315 ST5 TSST-1+ e S-70 TSST-1+ determinaram artrite grave, intermediária e discreta, respectivamente. No segundo trabalho caracterizamos a artrite causada pela cepa ATCC 19095 SEC+. Este tipo de artrite se caracterizou por elevado escore clínico associado à proliferação sinovial, inflamação intensa, formação de “pannus”, destruição da cartilagem e erosão óssea. A análise da expressão local de fatores de transcrição indicou expansão acentuada de células Th1 e Th17 nas lesões. No último manuscrito, avaliamos o efeito terapêutico da combinação do antibiótico bactericida cloxacilina com o imunomodulador tacrolimus. A administração destas duas drogas foi nemos eficaz no controle da doença do que o antibiótico administrado isoladamente
Keywords: Estafilococos; Staphylococcus aureus; Artrite - Tratamento; Articulações - Doenças; Antibióticos - Efeito fisiológico; Infecções estafilococicas; Antibiotics Physiological effect